Study of the mechanical, electrical and morphological properties of PU/ MWCNT composites obtained by two different processing routes - KHAN, UMAR; COLEMAN, JONATHAN NESBIT (Elsevier, 2012)
A comparative study of the influence of processing route on polyurethanes (PU)/ Multiwalled carbon nanotube (MWCNT) composites mechanical and electrical properties and also morphology was undergone employing two differentiated processing methods, solvent casting and buckypaper infiltration, for producing PU composites with low, medium and high mass fractions of acid treated MWCNT, and with no covalent linkages between the matrix and the nanotubes. As for example, with a MWCNT mass fraction of ~ 18 wt% the second method produced stiffer (270 MPa), lighter (948 kg m-3) and more electrically conductive (1.8 S cm-1) composite while the first one gave softer (111 MPa) and more ductile (141%) materials. These properties differences are related to the different PU/MWCNT dispositions obtained through each synthesis route. Nanotubes percolating concentration is found to be crucial on composite properties evolution and a preferential interaction of MWCNT with PU hard segments is observed for solvent cast composites.
PUBLISHED
Keywords: Condensed matter physics; A. Carbon Nanotubes; A. Polymer-matrix composites (PMCs)l